Validity of Obviousness in the Patent Process: A Case Study of Aktiebolaget (LOSEC) - Lai, Jessica (Victoria University of Wellington Law Review, 2007)
The granting of patents is qualified by the assessment of whether the said invention is obvious or involved an inventive step, and has some utility. The obviousness inquiry, based on the Windsurfing test, is a factual and objective inquiry, but its evaluative nature inherently requires some degree of subjective opinion or intuition from patent examiners and courts. The resultant uncertainty is demonstrated by the different outcomes of the Aktiebolaget cases heard around the world, where dependence on the notional person and derived expert witnesses is such that different results developed from the same facts and expert witnesses. This paper looks at the validity of the obviousness inquiry in light of these uncertainties. It concludes that invention duplication exercise evidence from the Australian Aktiebolaget case would be the most beneficial type of expert evidence for the current obviousness standard as it stands. However, it also find that obviousness may not be needed at all and that removing the inquiry may not be as detrimental as it first appears, but economic studies would be required to see its true effect.